Stock Market Reaction towards the Announcement of Indonesian Presidential Election Results - Ika Permatasari; Dian Anita Nuswantara; Alvin Rizani (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
There are several factors influence stock market reactions, namely political events. This paper uses event study methodology to study the stock price reaction to political events, particularly the official announcements of Indonesian Presidential Election results of 2004, 2009, and 2014 by General Election Commission. The event window was twenty-nine days (fourteen days before the event, during the event, and fourteen days after the event). By using stocks of the LQ45 category, we analyzed stock market reactions and average abnormal return around the official announcement of 2004, 2009, and 2014 Presidential Election. Other factor, i.e. quick count, is also discussed in this study as it influenced to the stock market reactions. Keywords: political event, Presidential Election, stock market reaction, average abnormal return